2015
DOI: 10.30827/digibug.53765
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study on EFL Teachers’ Beliefs About the Teaching and Learning of English in Public Education

Abstract: Teachers' beliefs have been a fascinating topic for researchers for the amount of input they can provide for reflection and the improvement of the teaching and learning of English. This case study aims at identifying the beliefs held by a group of sixteen Chilean EFL teachers who work in public secondary education. A semi-structured interview and a Likert type survey are used to collect data from the participants. Semantic content analysis and the Atlasti qualitative software are used to transcribe, code, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…It can be usefully used to arrange, reassemble, and manage materials in systematic ways. Furthermore, it has been proved effective in education, teaching, and applied linguistic studies [62][63][64]. The use of ATLAS.ti includes six main steps or stages.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…It can be usefully used to arrange, reassemble, and manage materials in systematic ways. Furthermore, it has been proved effective in education, teaching, and applied linguistic studies [62][63][64]. The use of ATLAS.ti includes six main steps or stages.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Expert EFL teachers have more knowledge of learners, learning, and teaching and the ability to combine theoretical and practical knowledge, actively engage students in class and themselves in critical reflection, and respond to different contexts [12,17]. Taken together, the specific features of teachers' professional quality can be divided into two thematic groups: teacher beliefs [24,[35][36][37][38][39][40][41] and teaching capacity [8,10,17,24,[42][43][44][45][46][47].…”
Section: Research On Efl Teachers' Professional Qualitymentioning
confidence: 99%
“…This finding is in line with the research done by (M. Hidayat, 2017) that revealed that there is a relationship between teachers' beliefs and classroom practices related to classroom management. In addition, (Larenas, et al, 2015) also found that teachers should have flexibility in managing classroom activity. The roles of teachers are to decide the activity suitable for students' capacity to learn.…”
Section: Students Perceptions Of Teachers' Beliefs In English As a General Subjectmentioning
confidence: 99%
“…Teachers' beliefs affected the teaching and learning process in the classroom (Larenas, Hernandez, & Navarrete, 2015;Munoz & Escobar, 2012;Pajares, 1992). (I.…”
Section: Introductionmentioning
confidence: 99%